1979
DOI: 10.1172/jci109469
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depression of the Xenogeneic Cell-Mediated Lympholysis in Systemic Lupus Erythematosus

Abstract: A B S T R A C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A substantial component of systemic autoimmune disease such as lupus involves the breakdown of lymphocyte tolerance, primarily through the expansion of autoreactive CD4 + T cells that provide help to B cells, which can in turn produce autoantibodies with various specificities (1). Although comparatively less is understood about how CD8 + T cells contribute to disease progression, perturbations in CTL function are evident in lupus patients (2,3). Several groups, including ours, have now shown that a functionally competent CD8 + T cell compartment is required to restrict disease severity in lupus-prone mice (4)(5)(6)(7), and subsets of CD8 + T cells have been identified that can suppress excessive CD4 + T follicular helper cell help to B cells, which is essential for maintenance of self tolerance (8).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial component of systemic autoimmune disease such as lupus involves the breakdown of lymphocyte tolerance, primarily through the expansion of autoreactive CD4 + T cells that provide help to B cells, which can in turn produce autoantibodies with various specificities (1). Although comparatively less is understood about how CD8 + T cells contribute to disease progression, perturbations in CTL function are evident in lupus patients (2,3). Several groups, including ours, have now shown that a functionally competent CD8 + T cell compartment is required to restrict disease severity in lupus-prone mice (4)(5)(6)(7), and subsets of CD8 + T cells have been identified that can suppress excessive CD4 + T follicular helper cell help to B cells, which is essential for maintenance of self tolerance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the defects partially resolved with disease remission, a residual disorder persisted. The coexistence of this abnormal T cell membrane function with other discrete T cell dysfunctions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) …”
mentioning
confidence: 99%
“…[20][21][22] Additional serum factors such as antilymphocyte antibodies to surface antigens 23,24 could as well inhibit T-cell proliferative responses 25,26 or T-cell cytotoxic activities. 27…”
Section: T-cell Function In Slementioning
confidence: 99%